EXPLORING INDIVIDUAL FACTORS THAT LEAD TO SUCCESSFUL RESEARCH REGISTRY RECRUITMENT. (16th November 2018) - Crittenden, J; Kaye, L
Abstract: Higher education institutions are frequently challenged to identify older adults to participate in research investigations requiring human subjects. The development of older adult research registries is one way in which to address this issue. The experience of the University of Maine Center on Aging in the establishment of the Maine Older Adult Research Registry (MOARR) is instructive in identifying best practices for overcoming many of the traditional barriers to constructing and maintaining the integrity of such registries. MOARR is comprised of 110 research volunteers representing a state-wide cohort (31 males and 79 females fifty years of age and over). The most likely recruits have completed some college or else have a college/graduate degree and are comfortable using the internet. Recruitment strategies have been multi-faceted including reaching out to potential recruits at older adult resource fairs, through articles in magazines that cater to older Mainers, and announcements at Area Agencies on Aging. Providing subjects with financial incentives to participate and providing them an opportunity to identify the particular types of research that interest them the most is critical to attracting and maintaining a robust roster of subjects. Areas of particular research interest that have attracted the greatest numbers of subjects include: volunteering, bone/joint and muscle health, health aging/wellness, food/nutrition, brain/cognitive health, mental health, and technology. Techniques for keeping participants engaged in between assignments include the use of a research registry newsletter and highlighting the experiences of individuals who have recently had a research project assignment.